Shear strengthening and shear repair of 2-span continuous RC beams with CFRP strips - Abdul Samad, Abdul Aziz; Ali, Noorwirdawati; Mohamad, Noridah; Jayaprakash, J.; Kong, Fah Tee; Mendis, Priyan (American Society of Civil Engineers, 2017)
An experimental investigation on initially strengthened and repaired 2-span continuous RC beams with carbon fiber–reinforced polymer (CFRP) strips was conducted. Fourteen full-scale beam specimens were tested using a four-point bending test with a shear span to effective depth ratio ðav=dÞ of 2.5:3.5. This study presents and discusses several influences on the behavior of strengthened and repaired beams and shear strength prediction: the influence of shear span to effective depth ratio, CFRP contribution to shear, CFRP wrapping schemes, number of layers of CFRP strips, and CFRP orientation angle. At failure, the CFRP strips were observed to rupture and debond along the critical shear crack line of the beam. The shear strength prediction was adopted from the design provisions of the American Concrete Institute (ACI) and was compared with the experimental results. The ACI code model was observed to have underestimated the experimental results from 32 to 44% for Beam Group 1 ðav=d ¼ 2.5Þ, 34 to 44% for Beam Group 2 ðav=d ¼ 2.5Þ, and 14 to 18%for Beam Group 3 ðav=d ¼ 3.5Þ. The findings verify that the ACI code model gave an acceptable conservative prediction of the shear strength capacity of an initially strengthened or repaired 2-span continuous RC beam. DOI: 10.1061/(ASCE)CC.1943-5614.0000756. © 2016 American Society of Civil Engineers.